THE EFFECT OF USING INFORMATION SEARCH STRATEGY ON STUDENTS’ READING COMPREHENSION OF ANALYTICAL EXPOSITION TEXT AT ELEVENTH GRADE OF SMA NEGERI 1 SORKAM IN 2020/2021 ACADEMIC YEAR) - Asriani Hasibuan; Anna Maria Tarihohan (Universitas Potensi Utama, 2021)
The goal of this study is to see if the Information Search strategy has a significant impact on students' reading comprehension of analytical exposition texts in eleventh grade students at SMA Negeri 1 Sorkam in the 2020/2021 Academic Year. This study employs an experimental approach with a pre-experimental research design, as well as a pretest-posttest design for one group. There are 187 students in the eleventh grade, therefore the population is made up entirely of them. Purposivesampling is the sampling technique utilized in this study, and the sample size is 31 students. The researcher collects data using an observation sheet for data on the implementation of the Information Search technique and a test for data on the students' reading comprehension of an analytical exposition text. The use of the Information Search approach yielded a score of 3.5, which is considered